2011
DOI: 10.1007/s10577-011-9203-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome homeologies and high variation in heterochromatin distribution between Citrus L. and Poncirus Raf. as evidenced by comparative cytogenetic mapping

Abstract: The genus Citrus is well-known for its economic importance and complex taxonomy. Only three to six Citrus taxa are considered true biological species, among them is Citrus medica, the citron. Previous studies based on chromomycin A3 (CMA)/4',6-diamidino-2-phenylindole staining showed that the citron has a homomorphic karyotype, consisting of four distinct chromosome types according to the CMA(+) heterochromatin distribution. Based on the pattern of CMA(+) bands and the hybridization of 25 bacterial artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…However, no indication of paracentric inversion was found in meiosis of Citrus × Poncirus hybrids [Agarwal, 1987b]. Compared BAC-FISH maps [Mendes et al, 2011] and genetic maps [Ollitrault et al, 2012] between Citrus and Poncirus species also suggested conservation of marker orders. Therefore, the possibility of repeated transposition events placing these nomad sites close together de novo in other chromosome pairs should be considered.…”
Section: De Novo Formation Of 5s-45s Rdna Linkagementioning
confidence: 86%
See 2 more Smart Citations
“…However, no indication of paracentric inversion was found in meiosis of Citrus × Poncirus hybrids [Agarwal, 1987b]. Compared BAC-FISH maps [Mendes et al, 2011] and genetic maps [Ollitrault et al, 2012] between Citrus and Poncirus species also suggested conservation of marker orders. Therefore, the possibility of repeated transposition events placing these nomad sites close together de novo in other chromosome pairs should be considered.…”
Section: De Novo Formation Of 5s-45s Rdna Linkagementioning
confidence: 86%
“…For example, if one of the 2 bands of a C chromosome undergoes a strong size reduction, the chromosome will look like a D type, or vice-versa [Moraes et al, 2007b]. Change from a D-type chromosome to a C or F type, for example, seems to have occurred several times in the subfamily Aurantioideae [Barros e Silva et al, 2010;Mendes et al, 2011]. In M. paniculata , a D chromosome pair was previously misinterpreted as a B pair because the occurrence of a secondary constriction in the CMA band [Guerra et al, 2000], but when observed with FISH, it became clear that the correct formula was 2C + 14D + 2F [Barros e Silva et al, 2010].…”
Section: Variation Of Cma Bands and Rdna Sites In An Apparently Stablmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the Citrus cultivars were classified as heteromorphic in respect to their banding pattern (homologue chromosomes showed distinct heterochromatin distributions) and a minority as homomorphic (Cornélio et al 2003;Yamamoto and Tominaga 2003;Moraes et al 2007a (Cornélio et al 2003;Yamamoto and Tominaga 2003;Carvalho et al 2005;Moraes et al 2007a, b;Guerra 2009; Barros e Silva et al 2010;Mendes et al 2011). The heteromorphic accessions are considered of hybrid origin, whereas homomorphic accessions might be pure or true species (Guerra 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Because these clones showed unique signals without blocking DNA in L. japonicus , it is probable that the dispersed hybridization pattern had been caused due to the presence of moderately repetitive sequences from these genomic regions in L. uliginosus that are present in lower copy number in L. japonicus . The difference in the hybridization pattern of the same BAC between species was also observed in a comparative mapping in Citrus [Mendes et al, 2011]. In Daucus , 2 BACs from carrot could not be mapped in wild species [Iovene et al, 2011].…”
Section: Discussionmentioning
confidence: 59%